Intelligibility of Nepali English Vowels: Rationales for Teaching Pronunciation - Chalise, Krishna Prasad (Nepalese Linguistics, 2025)
This paper has investigated the possible challenging vowels for the mutual intelligibility between NE (Nepali English) and GAE (General American English) based on internal and external masking and functional load. It is based on the data from secondary sources. The finding is that there is a remarkable intelligibility gap between NE and GAE because of internal and external masking, and phonetic distinctiveness between the corresponding vowels in them. Pronunciation is crucial for intelligibility, comprehension, and overall language proficiency. Still, it is often viewed as incidental to other language skills and is not included in textbooks, the evaluation system, and teacher training programs. For intelligible pronunciation, the listener should easily identify the phonological content of the speaker. For this purpose, they should activate both analytical skills (identifying and discriminating the phonetic features) and motor skills (articulating the phonetic features). This achievement is possible through rigorous pronunciation training based on the findings from empirical research.